Pomalidomide and lenalidomide regulate erythropoiesis and fetal hemoglobin production in human CD34+ cells - Laure A. Moutouh-de Parseval; Dominique Verhelle; Emilia Glezer; Kristen Jensen-Pergakes; Gregory D. Ferguson; Laura G. Corral; Christopher L. Morris; George Muller; Helen Brady; Kyle Chan (The Journal of Clinical Investigation, 2007)
Sickle-cell disease (SCD) and β thalassemia constitute worldwide public health problems. New therapies, including hydroxyurea, have attempted to augment the synthesis of fetal hemoglobin (HbF) and improve current treatment. Lenalidomide and pomalidomide are members of a class of immunomodulators used as anticancer agents. Because clinical trials have demonstrated that lenalidomide reduces or eliminates the need for transfusions in some patients with disrupted blood cell production, we investigated the effects of lenalidomide and pomalidomide on erythropoiesis and hemoglobin synthesis. We used an in vitro erythropoiesis model derived from human CD34+ progenitor cells from normal and SCD donors. We found that both compounds slowed erythroid maturation, increased proliferation of immature erythroid cells, and regulated hemoglobin transcription, resulting in potent induction of HbF without the cytotoxicity associated with other HbF inducers. When combined with hydroxyurea, pomalidomide and, to a lesser extent, lenalidomide were found to have synergistic effects on HbF upregulation. Our results elucidate what we believe to be a new mechanism of action of pomalidomide and lenalidomide and support the hypothesis that pomalidomide, used alone or in combination with hydroxyurea, may improve erythropoiesis and increase the ratio of fetal to adult hemoglobin. These findings support the evaluation of pomalidomide as an innovative new therapy for β-hemoglobinopathies.
Issue version published: January 2, 2008